Ratio ut subiectum peccati : la razón como sujeto de pecado según Tomás de Aquino - Larraguibel Diez, Luis E. (Sapientia, 2021)
The moral order is more convenient to the will because the reason does not formally consider its object sub ratione as good or bad, but as true or false. However, our apprehensive and appetitive faculties influence the sinful consent of the will, making them a subject of sin: hence, we will analyze not only the sin of reason, but also that of sensuality. Finally, we will verify that ignorance -originating from reason- is the cause of all sin; we will establish its gravity in relation to its voluntariness and the influence of sensuality on it.